2023
DOI: 10.1002/cbdv.202200939
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, and Antimycobacterial Evaluation of Novel Tetrahydroisoquinoline Hydrazide Analogs

Abstract: A series of novel 2-substituted-5,7-dichloro-1,2,3,4-tetrahydroisoquinoline-6-carbohydrazide were designed, synthesized and structures were confirmed by analytical methods, viz., 1 H-NMR, 13 C-NMR and Mass spectrometry. Synthesized derivatives were evaluated for their anti-mycobacterial activity against Mycobacterium tuberculosis (Mtb) H37Ra. Among all the evaluated compounds, 10A25 containing biphenyl moiety exhibited significant inhibition with IC 50 4.7 μM. 10A19, with an electron-withdrawing Iodo group in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Our recently published work provides detailed procedures for synthesizing up to intermediate 10 . 29 Finally, the target molecules NFT-1 to NFT-26 were synthesized from 9(a–z) by treating with 5-nitrofuran-2-carboxylic acid via an acid-amine coupling reaction using HOB t , EDC·HCl, and DIPEA in DMF at 25 °C. In 1 H NMR, the disappearance of one proton of –NH 2 from around 4.5 to 4.8 ppm and the appearance of an additional new amide proton at around 11 ppm confirm the formation of carbohydrazide.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Our recently published work provides detailed procedures for synthesizing up to intermediate 10 . 29 Finally, the target molecules NFT-1 to NFT-26 were synthesized from 9(a–z) by treating with 5-nitrofuran-2-carboxylic acid via an acid-amine coupling reaction using HOB t , EDC·HCl, and DIPEA in DMF at 25 °C. In 1 H NMR, the disappearance of one proton of –NH 2 from around 4.5 to 4.8 ppm and the appearance of an additional new amide proton at around 11 ppm confirm the formation of carbohydrazide.…”
Section: Resultsmentioning
confidence: 99%
“…Apart from this, a few modern reports also suggested that the putative mode of action of antimycobacterial tetrahydroisoquinoline derivatives is through inhibition of InhA of MTB. 29,36 Based on these reported facts and rationale, targeting the InhA enzyme followed by disruption of mycobacterial cellular homeostasis may be the appropriate strategy for the current molecular docking study and hence we have chosen Mycobacterium tuberculosis InhA (PDB ID: 4OHU), for the docking studies of the titled compounds.…”
Section: Molecular Docking Analysismentioning
confidence: 99%
See 3 more Smart Citations